2022
DOI: 10.20517/cdr.2021.115
|View full text |Cite
|
Sign up to set email alerts
|

Potential mechanisms of resistance to current anti-thrombotic strategies in Multiple Myeloma

Abstract: Multiple Myeloma (MM) is a common haematological malignancy that is associated with a high rate of venous thromboembolism (VTE) with almost 10% of patients suffering thrombosis during their disease course. Recent studies have shown that, despite current thromboprophylaxis strategies, VTE rates in MM remain disappointingly high. The pathophysiology behind this consistently high rate of VTE is likely multifactorial. A number of factors such as anti-thrombin deficiency or raised coagulation Factor VIII levels may… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 73 publications
(176 reference statements)
0
2
0
Order By: Relevance
“…Bradbury et al reported on the thrombosis rates observed in the Myeloma IX and Myeloma XI phase 3 trials and disappointingly, thrombosis incidence rates at 6 months remained >10% in the later trial despite much higher rates of thromboprophylaxis (80.5% vs. 22.3%) 25 . The reasons behind this failure are not fully understood but are likely multifactorial 27 . Some studies have proposed the possibility of “heparin resistance” in MM and have sought to evaluate the role of thrombin generation testing, a test of global hemostasis, to evaluate heparin efficacy in MM disease but results have been conflicting thus far 28,29 …”
Section: Thrombosis In Multiple Myelomamentioning
confidence: 99%
See 1 more Smart Citation
“…Bradbury et al reported on the thrombosis rates observed in the Myeloma IX and Myeloma XI phase 3 trials and disappointingly, thrombosis incidence rates at 6 months remained >10% in the later trial despite much higher rates of thromboprophylaxis (80.5% vs. 22.3%) 25 . The reasons behind this failure are not fully understood but are likely multifactorial 27 . Some studies have proposed the possibility of “heparin resistance” in MM and have sought to evaluate the role of thrombin generation testing, a test of global hemostasis, to evaluate heparin efficacy in MM disease but results have been conflicting thus far 28,29 …”
Section: Thrombosis In Multiple Myelomamentioning
confidence: 99%
“…25 The reasons behind this failure are not fully understood but are likely multifactorial. 27 Some studies have proposed the possibility of "heparin resistance" in MM and have sought to evaluate the role of thrombin generation testing, a test of global hemostasis, to evaluate heparin efficacy in MM disease but results have been conflicting thus far. 28,29 A number of internationally validated and clinically utilized risk scores have been developed to stratify VTE risk in patients with solid tumors who may benefit from thromboprophylaxis with anticoagulant agents.…”
Section: Thrombos Is In Multiple Myelomamentioning
confidence: 99%